Diversity of commercially important grouper (Family: Epinephelidae) in Simeulue and Banyak Islands, Aceh, Indonesia - Nanda Muhammad Razi; Zainal A. Muchlisin; Mutia Ramadhaniaty; Adrian Damora; Firman M. Nur; Mohd Nor Siti-Azizah; Nur Fadli (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Grouper is one of the economically important fish groups in the Simeulue and Banyak Islands. However, data on the diversity of the grouper in this region is still limited. This study aimed to inventory the commercially important grouper in Simeulue and Banyak Islands. Sampling was carried out in April - September 2021 at sixteen locations around Simeulue and Banyak Islands. In total, 20 species of commercial grouper consisting of 6 genera were recorded during the study. Epinephelus was the most dominant genus with ten species, followed by Cephalopholis with four species. In addition, seventeen species (85%) were included in the Least Concern (LC), two species (10%) were categorized as Vulnerable (VU), and one species (5%) was Data Deficient (DD). This study provides a database of commercially important grouper in Simeulue and Banyak Islands that can be used to manage the fish group.